Mother empowerment in reducing the risk of stunting: An integrative review - Indanah Indanah; Nani Nurhaeni; Dessie Wanda; Ikeu Nurhidayah (Faculty of Nursing Universitas Padjadjaran, 2026)
Background: Stunting is a global chronic nutritional problem, with mothers playing a crucial role in its prevention. Mother empowerment is essential in reducing the risk and prevalence of stunting Purpose: This study aimed to identity and synthesize qualitative and quantitative research evidence on empowerment mothers to improving children’s nutritional status and reducing the risk of stunting. Methods: This research employed an integrative review methode, and its was registered with the International Prospective Register of Systematic Reviews as a reseach-implementation protocol (ID number CRD 42023415771). Eight databased were searched for relevant literature, including Embase, PubMed, ScienceDirect, Scopus, ProQuest, JSTOR, Taylor & Francis, and Google Scholar. The evaluation of articles quality used the 2018 version of the Mixed Methods Appraisal Tool. While content analysis was employed for data analysis. Results: The result indicated that 53 articles fulfilled the inclusion requirement, out of the 54,987 articles found during the search phase. The analysis resulted in the discovery six themes: Indicators of empowerment, factor influencing empowerment, instrument for measuring empowerment, intervention to improve maternal empowerment, impact of intervention base on empowerment indicators and Stunting interventions across countries. These themes collectively form a conceptual model of mother empowerment to reduce the risk of stunting in children. It can be concluded that mother empowerment, by considering various indicators, can increase mothers' active participation in reducing the risk of stunting in children. Conclusions: that mother empowerment, by considering various indicators, can increase mothers' active participation in reducing the risk of stunting in children. Integrating empowerment-based interventions into maternal and child health programs is recommended to improve nutritional outcomes and reduce the prevalence of stunting.